Stem Cell-Derived Extracellular Vesicles as Immunomodulatory Therapeutics - Yoojin Seo; Hyung-Sik Kim; In-Sun Hong (Stem Cells International)
Mesenchymal stem cells (MSCs) have been reported to possess regulatory functions on immune cells which make them alternative therapeutics for the treatment of inflammatory and autoimmune diseases. The interaction between MSCs and immune cells through paracrine factors might be crucial for these immunomodulatory effects of MSCs. Extracellular vesicles (EVs) are defined as bilayer membrane structures including exosomes and microvesicles which contain bioactive paracrine molecules affecting the characteristics of target cells. Recently, several studies have revealed that EVs derived from MSCs (MSC-EVs) can reproduce similar therapeutic impacts of parent MSCs; MSC-EVs could regulate proliferation, maturation, polarization, and migration of various immune effector cells and modulate the immune microenvironment depending on the context by delivering inflammatory cytokines, transcription factors, and microRNAs. Therefore, MSC-EVs can be applied as novel and promising tools for the treatment of immune-related disorders to overcome the limitations of conventional cell therapy regarding efficacy and toxicity issues. In this review, we will discuss current insights regarding the major outcomes in the evaluation of MSC-EV function against inflammatory disease models, as well as immune cells.